ANALYSIS OF FACTORS INFLUENCING THE PERFORMANCE OF STATE CIVIL SERVANTS IN THE ADMINISTRATIVE BUREAU OF THE REGIONAL SECRETARIAT LEADERS OF NORTH SUMATRA PROVINCE - Indra Kesuma; Heri Kusmanto; Indra Fauzan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to determine how much influence Individual Factors, Psychological Factors, and Organizational Factors have on the Performance of State Civil Apparatuses in the Administrative Bureau of the North Sumatra Regional Secretariat. The population used in this study is the State Civil Apparatus in the Administrative Bureau of the North Sumatra Regional Secretariat, which totaled 50 people, the sample is taken with the whole of the total population tau with a saturated sample. The analysis technique uses multiple linear regression analysis, and hypothetical tests t test, f test, and determination test. The results of the calculation results obtained by the calculation results obtained by the Fcount value of 25,533 with a significance of 0.000, while the Ftable at the 95% confidence interval or α = 0.05 is 2.723. By comparing the value of Fcount with Ftable, then Fcount (25,533) is greater than Ftable (2,723). The decision was that H0 was rejected and Ha was accepted, meaning that simultaneously the individual factor variables (X1), psychological factors (X2) and organizational factors (X3) had a very significant (high significant) effect on the performance of the employees of the North Sumatra Province Secretariat Leadership Administration Bureau. Meanwhile the coefficient of determination obtained with a value of 69.0% changes in the dependent variable (Performance of Employees of the North Sumatra Province Secretariat Leadership Bureau) can be explained by changes in Individual (X1), Psychological (X2) and Organizational (X3) Factors ). Meanwhile, the remaining 31% is explained by other factors outside the three variables described above, such as work experience, work ability, benefits, and leadership style.